The effects of protein support with various content on nutrition status and clinical outcomes in elderly malnourished cancer patients: Protein support ın elderly malnourıshed cancer patients - Parlak, Eda; Atalay, Betül Gülşen (Progress in Nutrition, 2021)
Aim: The aim of this study was to investigate the nutritional status and clinical outcomes of elderly malnourished cancer patients receiving oral or enteral nutrition with various protein content. Methods: This retrospective study included 19 cancer patients receiving the β-hydroxy-β-methylbutyrate (HMB) + glutamine (GLN) + arginine (ARG) (1st group) combination, 48 receiving only GLN content (2nd group) and 19 receiving standard enteral supplementation (3rd group). The nutritional status of the patients was analysed by nutritional risk screening (NRS-2002). Anthropometric measurement were taken and the biochemical parameters were analysed. All measurements were recorded twice, before and after nutrition therapy. Results: The hospital mortality rate was 7% (n=6) among all patients, and our two-year follow-up mortality rate was 36% (n=31). We observed no differences between the groups in the length of hospital stay, nutrition therapy duration and mortality (p>0.05). The mean NRS-2002 score was found to be statistically significantly different between the control and glutamine groups after nutrition therapy with lower scores in the glutamine group (p=0.001). Post-nutrition serum albumin levels were also higher in the glutamine group than in the control group (p=0.001). Conclusion: We observed that patients who received standard enteral nutrition had higher NRS-2002 scores and lower serum albumin levels compared to patients who receiving only GLN or HMB combination. We were unable to find a factor that could be a good predictor of survival. Other randomly controlled studies are needed to determine the effectiveness of HMB or only GLN use in cancer patients.